2014
DOI: 10.5547/01956574.35.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Determinants of Electricity Prices and the Impact of the German Nuclear Moratorium in 2011

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
2
15
0
1
Order By: Relevance
“…The price decrease, induced by wind, is less strong when the nuclear capacity is removed. This results are confirmed by findings of Thoenes (2011). (2010) and Gruet (2011).…”
supporting
confidence: 85%
“…The price decrease, induced by wind, is less strong when the nuclear capacity is removed. This results are confirmed by findings of Thoenes (2011). (2010) and Gruet (2011).…”
supporting
confidence: 85%
“…In the reduced-form world, some authors have suggested modeling power and fuels as cointegrated processes (cf. [47,18,44,74]), while others have suggested multi-commodity Lévy based models with various ways of capturing correlations between jumps and/or diffusion components. (cf.…”
Section: 4mentioning
confidence: 99%
“…Además, estos modelos se han usado para analizar otros aspectos del mercado eléctrico, como evaluar el impacto de permisos a emisiones y moratoria nuclear (Thoenes 2015), así como para relacionar los precios de electricidad entre los distintos estados de Estados Unidos (Park, Mjelde y Bessler, 2006).…”
Section: Literaturaunclassified